Translation of mechanical strain to a scalable biomanufacturing process for acellular matrix production from full thickness porcine bladders. (15th October 2021) - Ward, Ashley; Morgante, Debora; Fisher, John; Ingham, Eileen; Southgate, Jennifer
Abstract: Bladder acellular matrix has promising applications in urological and other reconstructive surgery as it represents a naturally compliant, non-immunogenic and highly tissue-integrative material. As the bladder fills and distends, the loosely-coiled bundles of collagen fibres in the wall become extended and orientate parallel to the lumen, resulting in a physical thinning of the muscular wall. This accommodating property can be exploited to achieve complete decellularisation of the full-thickness bladder wall by immersing the distended bladder through a series of hypotonic buffers, detergents and nucleases, but the process is empirical, idiosyncratic and does not lend itself to manufacturing scale up. In this study we have taken a mechanical engineering approach to determine the relationship between porcine bladder size and capacity, to define the biaxial deformation state of the tissue during decellularisation and to apply these principles to the design and testing of a scalable novel laser-printed flat-bed apparatus in order to achieve reproducible and full-thickness bladder tissue decellularisation. We demonstrate how the procedure can be applied reproducibly to fresh, frozen or twice-frozen bladders to render 8 × 8 cm 2 patches of DNA-free acellular matrix suitable for surgical applications.